DISORDERS OF HEMATOPOIESIS IN HYPOTHYROIDISM AND HYPERTHYROIDISM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article considers the influence of hypo- and hyperthyroidism on hematopoiesis processes. It is shown that hypothyroidism is characterized by normo- and microcytic anemia, caused by decreased erythropoiesis and impaired iron metabolism. Hyperthyroidism is characterized by relative polycythemia, changes in the leukocyte and platelet levels. It is emphasized that timely correction of thyroid status in most cases leads to normalization of blood parameters, however, some patients require additional therapy and examination to exclude concomitant pathologies.